Healthcare disparities amongst vulnerable populations of Arabs and Jews in Israel - Efrat Shadmi (BMC, 2018)
Abstract The complex nature of studying health and healthcare disparities in general, and in the context of the Israeli healthcare system in particular, is depicted in two recent IJHPR articles. The first examines Emergency Department (ED) waiting times in a tertiary children's hospital and the second examines disparities in the health care for people with schizophrenia of an ethnic-national minority. Contrary to other Israeli studies on wide disparities in health and healthcare, these studies show no disparities -  ED waiting times did not differ among Arab and Jewish children and report no differences in performance of Hemoglobin A1C tests or in surgical interventions in patients with cardiovascular disease between Arabs and Jews with schizophrenia. Thus, the studies reflect areas of equitable health care delivery within the Israeli healthcare system. Future studies should account for the fact that the phenomena of health and healthcare disparities is complex and should utilize rigorous methodologies to take into consideration the various factors that may affect the manifestation of differences amongst population groups. As a result, they may help detect disparities which may otherwise be missed.